Examining the influence of non-governmental organizations upon the long term outcomes of the involuntary community resettlement processes: with special reference to the Kariba case, Zambia - Sitambuli, Emma (Rhodes University, Faculty of Humanities, Department of Anthropology, 2016)
Researchers have clearly demonstrated that Development" Induced Displacement and Resettlement (DIDR) usually risks impoverishing people and that annually, millions are displaced as a result. Although the impacts and consequences of resettlement are known, over the next couple of decades, development projects will continue to be needed to meet the different demands of growing economies and populations, of especially developing countries, making relocation sometimes unavoidable. Hence, over the years, many scholars have developed conceptual frameworks to understand and explain the impoverishment risks inherent in the resettlement phenomenon; and how those can be anticipated so as to be positively counteracted through strategic interactions and the implementation of development activities. Generally, the majority of those development activities to improve resettlement outcomes have often been planned, funded, and executed by the government, albeit with mixed levels of success, yet the possibilities of other development institutions such as Non" Governmental Organizations (NGOs) have not been fully understood. However, a great deal of what is known about NGOs relates to their work in advocacy and activism to pressure governments to, for example, change relocation plans or raise awareness on the negative impacts of development projects on people and environment. Therefore, this thesis examines the influence of NGOs upon the on" going outcomes of the involuntary community resettlement processes. The empirical basis is ethnographic research, which integrated several resettlement conceptual frameworks and theories about NGOs to collect and analyse data. Fieldwork was carried out in four villages of Simamba i.e. Malata, Kafwakuduli, Nangoba and Hamukonde. Simamba is one of the riverine Gwembe chiefdoms resettled following the construction of the Kariba dam on the Zambezi River bordering Zambia and Zimbabwe. The ethnographic research for this thesis was conducted from 2013 to 2015. In this thesis, I demonstrate that spatial factors influenced the resettlement trajectory using evidence from Simamba's pre and post resettlement situation. I conclude by arguing that sustained contributions of the NGO type of development can positively influence the long" term outcomes of involuntary community resettlement processes, and that problems that occurred were largely related to the management of the community development activities by the NGO under study. Therefore, this thesis is relevant to resettlement and development studies in general.
Keywords: Uncatalogued